Naratif Sejarah Pembangunan Nizam-i Cedid dalam Pembaharuan Ketenteraan Uthmaniyyah Era Mahmud II, 1808-1839: The Historical Narrative of Nizam-i Cedid Development in the Ottoman Military Reforms under Mahmud II, 1808-1839 - Jamsari, Ezad Azraai; Baharudin, Muhammad Zharif; Safiai, Mohd Hafiz (Journal of Al-Tamaddun, 2025)
The Ottoman military reforms during the reign of Mahmud II (1808-1839) were not merely a reaction to the decline of influence and power of the Janissary corps, but rather a manifestation of the revival of Ottoman political rationality and governance vision that sought to integrate centralized power, technology, and modern discipline grounded in the principles of modernization. In confronting the geopolitical pressures posed by Russia and Europe, Mahmud II employed the military reform agenda as a vehicle to restructure Ottoman political authority, reinforce the sultan’s power, and curb the influence of the old oligarchy. This article aims to retrospectively examine the continuity of this reformist vision by tracing the historical legacy of the Nizam-i Cedid movement, which was revived in a new form through the establishment of the Segban-i Cedid and Asakir-i Mansure-i Muhammadiye, while also laying the foundation for political and military governance transformation in the nineteenth century. The study adopts a qualitative approach through the application of historical research design and content analysis. Data were collected using the documentation method, focusing on several reliable and authoritative sources. For data analysis, the study employed a descriptive approach through internal and external critique of relevant historical documents and texts. The findings argue that Mahmud II successfully revitalized and channelled the spirit of Nizam-i Cedid as the core of Ottoman military governance reform in the nineteenth century. Through the establishment of the Asakir-i Mansure-i Muhammadiye and the abolition of the Janissaries in 1826, Mahmud II restructured the social hierarchy of the military, strengthened fiscal control, and created a new form of governance that reoriented societal loyalty around the ideal of reconciling Islamic traditions with modern needs and aspirations of the time. Therefore, Mahmud II’s reform efforts should be understood not merely as a modernization of the military sphere, but as a broader political and administrative reform that transformed the Ottomans from a monarchical legacy into a sovereign modern gobernment, thus offering a deeper understanding of the dynamics of Ottoman military evolution across different eras.